2012
DOI: 10.1021/jm3008079
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Net Charge, Lipophilicity, and Side Chain Flexibility in Dmt1-DALDA: Effect on Opioid Activity and Biodistribution

Abstract: The influence of the side chain charges of the second and fourth amino acid residues in the peptidic μ opioid lead agonist Dmt-D-Arg-Phe-Lys-NH2 ([Dmt1]-DALDA) was examined. Additionally, to increase the overall lipophilicity of [Dmt1]-DALDA and to investigate the Phe3 side chain flexibility, the final amide bond was N-methylated and Phe3 was replaced by a constrained aminobenzazepine analogue. The in vitro receptor binding and activity of the peptides, as well as their in vivo transport (brain in- and efflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The increase was also apparent in the pA 2 values (pA 2 ( 21 ) 6.04 → pA 2 ( 22 ) 6.44). In a previous study, 39 we demonstrated that D-Arg 2 could be replaced by D-Cit, a modification that removes one positive charge in the peptide, without loss of BBB permeability. Hence, this modification was also carried out in the present study, to give 23 .…”
Section: Resultsmentioning
confidence: 92%
“…The increase was also apparent in the pA 2 values (pA 2 ( 21 ) 6.04 → pA 2 ( 22 ) 6.44). In a previous study, 39 we demonstrated that D-Arg 2 could be replaced by D-Cit, a modification that removes one positive charge in the peptide, without loss of BBB permeability. Hence, this modification was also carried out in the present study, to give 23 .…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, 125 I-LinS showed a relatively high liver uptake (15 min after iv injection), which was approximately three times higher compared to the other investigated enkephalins. Several studies have demonstrated that a decrease in the overall lipophilicity of liver targeting peptides suppresses their hepatic uptake [34,40]. LinS was predicted to be more lipophilic than the other three investigated enkephalin analogs, and thus this more lipophilic nature may contribute to the observed higher liver uptake and most likely also to the observed higher real brain penetration (besides active transport systems).…”
Section: Discussionmentioning
confidence: 99%
“…A rapidly growing body of evidence shows that many peptides, especially endogenous peptide analogs, do cross the BBB based on favorable chemical, physicochemical, and biological properties, including size, flexibility, biochemical properties of amino acids, lipophilicity, hydrogen-bonding, and 3D-conformation. Biomolecular adjustments of the lipophilic nature [7], charge, and H-bonding potential [17], is one strategy applied to improve the BBB permeability and deliverance of therapeutic peptides to the brain [40]. Passive diffusion as well as active transport mechanisms are addressed by this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Novoa et al [36] studied the effect of variation of the net charge, lipophilicity and side chain flexibility in Dmt 1 -DALDA ( 58 , Table 4) on opioid activity and biodistribution. [37].…”
Section: Investigational Opioid Receptor Agonistsmentioning
confidence: 99%